2011
DOI: 10.1007/s00134-010-2129-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucose variability measures and their effect on mortality: a systematic review

Abstract: ObjectiveTo systematically review the medical literature on the association between glucose variability measures and mortality in critically ill patients.MethodsStudies assessing the association between a measure of glucose variability and mortality that reported original data from a clinical trial or observational study on critically ill adult patients were searched in Ovid MEDLINE® and Ovid EMBASE®. Data on patient populations, study designs, glucose regulations, statistical approaches, outcome measures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 32 publications
2
108
1
1
Order By: Relevance
“…A systematic review reported that there were 13 different indicators to measure glucose variability 10. SD was one of the most common indicators.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review reported that there were 13 different indicators to measure glucose variability 10. SD was one of the most common indicators.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that our dataset contains more detailed information on potential confounders. For example, only half of the prior studies included a severity-of-illness indicator in their models, 13,[15][16][17][18]31 and few contained detailed data on comorbidities. In addition, there is no single established measure of GV, and prior studies have tested and reported on a variety of such measures.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by a recent systematic review, reporting bias may result in GV measures found to be more strongly associated with outcomes to be preferentially reported and published. 31 Another possibility is that the intensity of BG monitoring (and therefore the amount of data that is used to measure GV) may differ between critically ill patients in medical and surgical intensive care units and those with AMI. BG monitoring tends to be more frequent in medical/surgical intensive care units versus coronary care units.…”
Section: Discussionmentioning
confidence: 99%
“…The dosages were titrated every day in order to attain euglycemia within 5-7 days. During intervention patients were instructed to continue diet and physical exercise: a balindependent cohorts, which have been meta-analyzed [4]. Of note, the strong relationship between GV and diabetic complications [5][6][7][8], including cardiovascular complications [8,9], have been demonstrated, which may support the concept that GV can confer additional risk to the development of complications over that predicted by the mean glucose value alone [1].…”
Section: Methodsmentioning
confidence: 94%